Avaliação da velocidade de proliferação celular, citomorfometria e dano genético no campo de cancerização bucal : um estudo citopatológico - Paiva, Ricardo Losekann (2017)
Oral cytopathology may be used to monitor individuals exposed to risk factor for oral cancer. In this context, the study of field cancerization, a phenomenon involved in the initial stages of oral carcinogenesis, has gained relevance for the establishment of biomarkers that may identify individuals exposed to carcinogens with the greatest risk for developing oral cancer. The first article of this study aimed to compare cytopathological and histopathological characteristics of the clinically normal mucosa adjacent to oral squamous cell carcinoma. The nuclear area of cells obtained by cytological smear of this region was also analyzed and compared to that of individuals without lesions but exposed to smoking and/or alcohol and of patients not exposed to these risk factors. Ninety patients of both sexes over 40 years old were included. In patients with carcinoma, in addition to exfoliative cytology, tissue was obtained from the area adjacent to the tumor for histopathological examination. In smears stained with Papanicolaou, the nuclei of 50 intermediate cells were measured. Both histological sections and cytological smears were classified as low or high-risk. The sensitivity, specificity and accuracy of the cytopathological diagnosis in relation to the histopathological diagnosis, considered the gold standard, were 100, 75 and 75.86%, respectively. The mean nuclear area was significantly lower (p<0.05) in the patients not exposed to the risk factors in relation to the others. The cyto-histopathological comparison of the area adjacent to oral cancer showed good sensitivity, specificity and accuracy. In conclusion, this article demonstrated that nuclear area can be used to detect early cellular changes in the oral mucosa exposed to carcinogens and that mean percentage of nuclei larger than 100 μm2 is the most indicated method for the assessment of these changes. The second article aimed to assess genetic damage and cell proliferation rate in the field of cancerization, i.e., the clinically normal mucosa adjacent to oral carcinoma. Cytologic smears from the same scrapes used in the first article were stained with silver and with the Feulgen reaction. The mean number of AgNORs/nucleus and micronuclei (MN) was significantly higher (p<0.05) in the Tobacco/Alcohol and Oral Cancer Groups than in the Control Group. Conversely, the mean number of NBUDs was higher in the Control Group compared with the other groups. The number of AgNORs/nucleus and MN/1,000 cells provide evidence of initial oral carcinogenesis at field cancerization areas. Cutoff values for inclusion of individuals exposed to carcinogens in longitudinal monitoring were ≥ 3.38 AgNORs/nucleus and/or ≥ 3 MN/1,000 cells. A prospective model including the biomarkers assessed in this study was proposed.